Dividend Changes And Future Profitability: Evidence From Malaysia - Siew-Peng Lee,; Mansor Isa,; Wei-Ling Lim, (Asian Academy of Management Journal of Accounting and Finance, 2012)
Most of the previous studies on dividends in Malaysia focus on dividend signalling; there is hardly any published evidence relating dividend changes to firms’ profitability. Using a total of 2,396 dividend changes of companies listed on Bursa Malaysia over the period 1998-2007, this study investigates the relationship between dividend changes and future profitability of firms. We find that dividend changes are strongly related with contemporaneous earnings changes, weakly related with one year ahead of earnings changes and largely unrelated with earnings changes beyond one year. Further, we find weak evidence that the size of dividend changes is related to future profitability. We also find that dividend increases in the recovery years of the Asian 1997 financial crisis are related with one year ahead of earnings increases. Our results also suggest that dividend stability may be directly related with information content on future earnings.